An Unusual Case of Trisomy 18 Associated with Paucity of Bile Ducts. (1st October 2013) - Kahramaner, Zelal; Erdemir, Aydin; Cosar, Hese; Turkoglu, Ebru; Sutcuoglu, Sumer; Turelik, Ozlem; Cumurcu, Suheyla; Bayol, Umit; Ozer, Esra
<x xml:space="preserve">Abstract</x> A case of neonatal cholestasis associated with Trisomy 18 (Edward's syndrome) is presented. A 3-day-old boy was referred to our clinic due to respiratory distress, elevated serum direct bilirubin levels, a systolic heart murmur, growth restriction and micrognathia. Liver biopsy and chromosomal analysis revealed paucity of intrahepatic bile ducts and Trisomy 18. Extrahepatic biliary atresia was reported in only a few patients with Trisomy 18. To our knowledge, we described for the first time a patient with Trisomy 18 and neonatal cholestasis associated with paucity of interlobular bile ducts.